1980
DOI: 10.1093/oxfordjournals.aje.a113035
|View full text |Cite
|
Sign up to set email alerts
|

Reye Syndrome in Ohio, 1973–1977

Abstract: Some major epidemiologic features of Reye syndrome have been elucidated since the first description of this clinical entity. Multiple studies have shown an association with epidemic influenza B and endemic varicella. Little population data are available on age, sex, race, geographic distribution, and secular trends. A five-year retrospective population-based study of 190 Ohio residents diagnosed with Reye syndrome from January 1, 1973-December 31, 1977, is reported here. The temporal relationships between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…With the finding of a lower 10-year incidence of Reye's syndrome in New Brunswick than had been previously reported in Michigan and Ohio using similar case-finding techniques [3,4], plus the absence of any apparent association with exposure, we concluded that there was no epidemic of Reye's syndrome in New Brunswick and no association between exposure to budworm spraying and its occurrence in the province. The forest industry carried out its customary spraying program in June, and the crisis was apparently settled.…”
Section: Epiloguesupporting
confidence: 58%
See 1 more Smart Citation
“…With the finding of a lower 10-year incidence of Reye's syndrome in New Brunswick than had been previously reported in Michigan and Ohio using similar case-finding techniques [3,4], plus the absence of any apparent association with exposure, we concluded that there was no epidemic of Reye's syndrome in New Brunswick and no association between exposure to budworm spraying and its occurrence in the province. The forest industry carried out its customary spraying program in June, and the crisis was apparently settled.…”
Section: Epiloguesupporting
confidence: 58%
“…Reye's syndrome had always been a rare disease, with reported annual incidence rates of one to three cases per year per 100,000 children under 18 years of age in Michigan and Ohio, where intensive case-finding techniques had been used [3,4]. The disease was known to be seasonal, with higher incidence in winter and spring, particularly during epidemics of influenza or chicken pox.…”
Section: What Is Reye's Syndrome?mentioning
confidence: 99%